(untitled) (Conference Series, 2021)
As a highly regulated sectors, banks should be able to manage various risks by implementing Good Corporate Governance through detailed Standard Operating Procedure (SOP). Currently, financial sectors in Indonesia are dominated by Millennial’s workforce whom prefer digital way of communication rather than conventional reading. Thus, one multinational bank in Indonesia implements Video Learning SOPs to accommodate Millennials. The purpose of this study is to understand the adoption of Video Learning SOPs in financial sector using UTAUT. The study is quantitative research with availability sampling. 1077 respondents gathered using online questionnaire and analyzed using Partial-Least Square Structural Equation Model (PLS-SEM). Perceived interactivity was included as additional factors and the moderation of Age also analyzed. The results showed that there was significant relation between Performance Expectancy, Effort Expectancy, Social Influence, and Perceived Interactivity with Behavioral Intention to use Video Learning SOPs whereas Perceived Interactivity and Performance Expectancy also significantly impact it. It also revealed that there was positive but insignificant moderating effect of Age on the Behavioral Intention to use Video Learning SOPs. This research is among the first that reveals significant factors that impacting the adoption of Video Learning SOPs in a highly regulated industry.